What does US money market mutual fund reform portend for the European Union? - Craig M. Lewis; Christian Schlag (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
On 23 July 2014, the U.S. Securities and Exchange Commission (SEC) passed the "Money Market Reform: Amendments to Form PF ," designed to prevent investor runs on money market mutual funds such as those experienced in institutional prime funds following the bankruptcy of Lehman Brothers. The present article evaluates the reform choices in the U.S. and draws conclusions for the proposed EU regulation of money market funds.
Keywords: 330; money market funds; liquidity runs; floating net asset value (FNAV)